Effect of Gas Diversion Device on Performance of Microchannel Evaporator - Qin Haiyan; Chen Hua; Xu Geng (Zhileng xuebao)
The uneven distribution of refrigerant flow in a micro-channel evaporator leads to the dry-out phenomenon that deterioratesthe heat transfer performance. In this study, a dual-circuitrymicro-channel evaporator performance test platform was established to investigate the influence of a gas diversion device on the heat transfer performance of the evaporator and the uniformity of refrigerant distribution in a flat tube. The results showed that the maximum latent heat of the phase change was the same as that of the liquid phase refrigerant evaporation, giving rise to the small differences in heat transfer and heat transfer coefficient between the two structures. The maximum difference was only 0.5% and 6.9%, respectively. However, the length of the two-phase section increased by 87.3%, and the superheat of the two structures decreased considerably. When the wind speed was 3 m/s, the superheat difference between the two structures was 44.4%. The distribution of refrigerant between the flat tubes tends to be consistent; the uniformity is improved; the dry steaming phenomenon is relieved.